2004
DOI: 10.1098/rspb.2004.2810
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in cultures of the dinoflagellate Amphidinium carterae during culture senescence and darkness

Abstract: The study of cell death in higher plants and animals has revealed the existence of an active ('programmed') process in most types of cell, and similarities in cell death between plants, animals, yeast and bacteria suggest an evolutionarily ancient origin of programmed cell death (PCD). Despite their global importance in primary production, information on algal cell death is limited. Algal cell death could have similarities with metazoan cell death. One morphotype of metazoan PCD, apoptosis, can be induced by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 54 publications
(76 reference statements)
3
55
0
Order By: Relevance
“…is also thought to undergo PCD (displaying an apoptotic morphology) due to heat stress (Dunn et al, 2002). However, in the dinoflagellate Amphidinium carterae, cell death in darkness, and during culture senescence, results in similar morphological changes without definitive apoptotic characteristics (Franklin & Berges, 2004). Mortality in A. carterae shows greatest morphological similarity with paraptosis (see Table 1) -an alternative outcome of PCD (Sperandio et al, 2000), which was originally observed in mammalian nerve tissue.…”
Section: Population Crashes and Cell Death In Dinoflagellatesmentioning
confidence: 99%
See 1 more Smart Citation
“…is also thought to undergo PCD (displaying an apoptotic morphology) due to heat stress (Dunn et al, 2002). However, in the dinoflagellate Amphidinium carterae, cell death in darkness, and during culture senescence, results in similar morphological changes without definitive apoptotic characteristics (Franklin & Berges, 2004). Mortality in A. carterae shows greatest morphological similarity with paraptosis (see Table 1) -an alternative outcome of PCD (Sperandio et al, 2000), which was originally observed in mammalian nerve tissue.…”
Section: Population Crashes and Cell Death In Dinoflagellatesmentioning
confidence: 99%
“…One possible functional role of such a pathway in unicellular algae (and yeast) is to recycle the organic remains of cells for use by conspecifics (Gomez et al, 1974;Frohlich & Madeo, 2000). This idea is controversial and requires a convincing demonstration of conspecific nutritional (or other) benefit resulting from the cell death of some proportion of the cells (Franklin & Berges, 2004). That cell death could provide nutritional benefit for remaining conspecifics is an idea that is easier to accept for yeast, because yeast cell division can be clearly asymmetric (e.g.…”
Section: Pcd In Chlorophytes: 'Functional' and 'Non-functional' Pcdmentioning
confidence: 99%
“…However, several other species of microalgae have been proposed to undergo programmed cell death (PCD), necrosis (Dunn et al, 2002) as well as a range of intermediate cell death modes (Franklin and Berges, 2004;Franklin et al, 2006;Jiménez et al, 2009). Because it results in the complete loss of the organism, the occurrence of PCD in unicellular cells seems counterintuitive.…”
Section: Introductionmentioning
confidence: 99%
“…Heat-killed cells have a shrunken appearance, with cytoplasmic bunching and reduced chlorophyll fluorescence. These characteristics are similar to the 'senescent' appearance of microalgae in nutrientexhausted batch cultures, which are also called 'chlorotic' cells (La Roche et al 1993, Franklin & Berges 2004). Therefore, heat-killed cells may offer a reasonable physical simulation of natural dead cells, if one accepts that natural cell death in nature is caused primarily by nutrient starvation and results in the chlorotic state.…”
Section: Resultsmentioning
confidence: 67%